Realizing Indigenous jurisdiction in environmental decision-making in historic treaty lands: An Alberta Treaty 8 case study ... - Baccarini Macias Gimenez, Rebeca (University of Alberta Library, 2023)
SSHRC IG awarded 2024:The current Alberta framework for considering industrial cumulative adverse effects on treaty territories has not been able to account for Indigenous ways of life, perspectives, and law. Cumulative impacts of developments such as oil and gas, hydropower dams, and tracking are a clear result of the provincial Crown's piecemeal and unilateral approval of projects as the proxy for environmental decision-making. A legal and policy framework that allows for collaborative governance with First Nations taking a regional and strategic view of Indigenous territories is necessary. The overarching goal of the project Realizing Indigenous jurisdiction for environmental decision-making in historic treaty lands is to develop knowledge that supports the reform of Alberta's laws and policies to address the issue of cumulative impacts of development on Indigenous peoples' treaty rights and their ways of life, using the framework of joint environmental decision-making. The project team will use a case ...